Analisis Dampak Program MBG terhadap Antusiasme Siswa Datang ke Sekolah di UPTD SDN Kamal 1 - Elvira Oliviasari; Nadhyva Maulida Farih; Putri Hamimah; Rika Wulandari; Yuni Andari (ARZUSIN, 2025)
This study is motivated by the importance of fulfilling students’ nutritional needs as a key factor supporting the success of teaching and learning processes in elementary schools, given that poor nutritional quality often leads to reduced concentration, learning enthusiasm, and attendance. The study aims to analyze the impact of implementing the Program Makan Bergizi Gratis (MBG) at UPTD KAMAL 1 Bangkalan on students’ attendance, motivation, and learning atmosphere. A qualitative approach with a case study design was employed, involving students and teachers as research participants. Data were collected through interviews, direct observations, and documentation, and were analyzed thematically to identify patterns of behavioral change and dynamics in students’ activities after participating in the program. The findings show that the MBG Program has a significantly positive impact on students’ enthusiasm and discipline, as reflected in increased attendance, reduced tardiness, and high motivation to come to school in the morning. Shared meal activities create a warm and inclusive atmosphere, strengthen social interaction among students, and foster closer relationships between teachers and students, while simultaneously enhancing students’ focus and readiness to learn after breakfast. These findings reinforce the understanding that adequate nutrition has a direct effect on students’ mental readiness, emotional comfort, and engagement in the learning process. The study concludes that the MBG Program not only contributes to meeting students’ nutritional needs but also improves the overall quality of the learning process, and offers practical implications for schools and government in designing sustainable nutrition programs as an effort to enhance the quality of education at the elementary level.